Association between Chronic Allergic Rhinitis and Sleep Quality Disturbances among Young Adults. A Cross-Sectional Clinical Study - ZAMN, SAIRA; UPPAL, ATHAR ADNAN; SHAHBAZ, AYESHA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Chronic allergic rhinitis (CAR) is a common IgE-mediated upper airway inflammatory disease, which is often accompanied by nasal congestion, rhinorrhea, and sneezing. There is a growing body of evidence indicating that CAR has a major disturbance effect on sleep quality, especially in young adults who are already exposed to various academic and psychosocial stressors. Aims: To evaluate the relationship between chronic allergic rhinitis and sleep quality disturbances in young adults with the aid of a uniform sleep assessment instrument. Methods: Cross-sectional clinical study will be done in an ENT outpatient clinic between January and December 2024. One hundred and fifty (150) individuals of ages 18-35 years old were randomized to participate in the study with 75 participants being patients of CAR and other 75 controls. The level of sleep quality was measured through use of the Pittsburgh Sleep Quality Index (PSQI). Demographic data, severity of the symptoms, and triggers were noted. A chi-square, t-tests, and a logistic regression of p = 0.05 were used to conduct statistical comparisons. Results: CAR group scored considerably greater global PSQI scores in comparison with controls (9.2 ± 3.4 vs. 4.1 ± 2.2; p < 0.001). A lower sleep quality (PSQI > 5) was found in 69.3% of CAR and 25.3% among the controls (p < 0.001). Constant and moderate-to-severe CAR was closely linked to sleep disturbance. The logistic regression revealed that CAR is an independent finding that predicts poor sleep quality (adjusted OR 3.84; 95% CI: 2.146.91). Conclusion: CAR has a considerable negative effect on sleep quality in young adults, and persistent and moderate-severe symptoms are the factors that lead to an adverse effect on sleep. Sleep quality assessment should be performed regularly among CAR patients to ensure complete management and the general condition of well-being.